Realizacja projektów z Budżetu Obywatelskiego Województwa Łódzkiego „Łódzkie na plus” na przykładzie Biblioteki Pedagogicznej w Zgierzu, Filia w Łęczycy .......... 151 - Jankowska, Bogusława (Skąd się biorą czytelnicy?, 2025)
THE IMPLEMENTATION OF THE PROJECT ‘THE GIFTED FROM THE POMERANIA’ IN THE POMERANIAN PEDAGOGICAL LIBRARY IN GDAŃSKThe article presents the efforts made by the Pomeranian Pedagogical Library in Gdańsk in 2017-23 within the Project ‘Zdolni z Pomorza’ (The Gifted from Pomerania), financed by EU grants. The library ran seven Pomeranian schoolchildren Science Conferences, eight author’s meetings, five different thematic workshops, and thirteen meetings of the film discussion club. The project and all its activities were addressed to gifted teenagers from the Pomeranian Province.